Wildfire Spread Modeling in Pau Furado State Park Using Cellular Automata and Genetic Algorithms - Ferreira, Maria Eugênia A.; Lima, Danielli A.; Martins, Luiz Gustavo A. (Anais do Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais (WCAMA); 2025: Anais do XVI Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais, 2025)
Wildfire spread has intensified in Brazil, particularly in biomes such as the Cerrado, due to climate change and environmental degradation. This study proposes a heterogeneous wildfire spread model based on cellular automata (CA), optimized using genetic algorithms (GA), to simulate fire propagation in areas with different vegetation types, such as Pau Furado State Park. The model accounts for the interaction between wind, vegetation, and soil conditions, and employs the GA to adjust parameters such as fire intensity and wind direction, aiming to align the simulations with reference data. The results showed that the model accurately reproduced fire spread dynamics, demonstrating the effectiveness of GA in parameter optimization.